Distribution of enzymatic and alkaline oxidative activities of phenolic compounds in plants - Jorma Kim; Maija Pälijärvi; Maarit Karonen; Juha-Pekka Salminen (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In this study, we screened 287 plant tissue samples from 175 plant species for their phenolic profiles. The samples were oxidized enzymatically in planta or at high pH in vitro to determine how these two oxidative conditions would alter the initial polyphenol profiles of the plant. Compounds that contained a pyrogallol or dihydrox-yphenethyl group were highly active at pH 10. Enzymatic oxidation favored compounds that contained a catechol group, whereas compounds containing a pyrogallol group or monohydroxysubstituted phenolic moieties at most were oxidized less frequently. This study gives a broad overview of the distribution and alkaline oxidative activities of water-soluble phenolic compounds in plants as well as the enzymatic oxidative activities of various plant tissues.